PENERAPAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL)UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SD NEGERI 035 SEKELADI KECAMATAN TANAH PUTIH - Erfina '; Mahmud Alfusari; Lazim.N ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem this research is the low learning outcomes fifth grade science students SD Negeri 035 Sekeladi, from the average value of students is 59.75. Of the 20 students who achieve above KKM only 8 (40%), while that has not reached the KKM 12 (60%), KKM predetermined is 70. The problems "whether the application Contexual approach Teaching and Learning (CTL) can improve learning outcomes IPA in class V students of SD Negeri 035 Sekeladi? Research objective IPA improve learning outcomes through the implementation of CTL approach in SD Negeri 035 Sekeladi. The subjects were fifth grade students of SD Negeri 035 Sekeladi the number of students 20 people, consisting 13 women 7 men. The study design was a Class Action Research. This study conducted in two cycles, four meetings by discussing the lessons and twice held the final repetition of cycle. With the implementation oapplication of the CTL approach can improve student learning outcomes IPA, the percentage of completeness of student learning outcomes in basic score 59.75 so as to 40% and increased to an average of 67, and to 75% in the first cycle, while in the second cycle increased 78.75 to be 90%, percentage of teachers increased activity in the first cycle is 67.2%, second cycle increased to 85.9%. The percentage of student activity increased in the first cycle to 68.8%, while second cycle increased 89%. above explanation can be concluded application CTL approach can improve learning outcomes fifth grade science students of SD Negeri 035 Sekeladi.Keywords: Approach Contexual Teaching and Learning (CTL), the Science Learning Students